A graphene-loaded noble metal composite powder and a preparation method thereof, and a Schottky device
By uniformly distributing precious metal nanoparticles in graphene, the problem of easy agglomeration of graphene is solved, and the Schottky barrier height and conductive properties of Schottky devices are improved.
Patent Information
- Application Number
- CN202111626021.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-12-28
AI Technical Summary
Graphene is prone to agglomeration, resulting in a low Schottky barrier height of the resulting device, affecting device performance.
By mixing graphene oxide solution, precious metal precursor solution and reducing agent, and carrying out hydrothermal reduction reaction, a graphene-loaded precious metal composite powder is prepared, and precious metal nanoparticles are evenly distributed on the surface and between the graphene layers to inhibit the agglomeration of graphene.
It realizes that graphene is not easy to agglomerate, improves the Schottky barrier height and ideal factors of Schottky devices, and improves the conductive performance and performance stability of the device.
Smart Images

Figure CN114300532B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of Schottky devices, and in particular to a graphene-loaded noble metal composite powder and a preparation method thereof, and a Schottky device. Background Art
[0002] The metal-semiconductor contact characteristics are widely used in semiconductor devices and integrated circuits. Any semiconductor device has a common basic structure, namely the input of energy and the functional output after the operation of the device, and the hub of this input and output is the metal-semiconductor contact.
[0003] Schottky contact refers to the bending of the semiconductor energy band at the interface when metal and semiconductor materials come into contact, forming a Schottky barrier. The Schottky junction is similar to the PN junction and has nonlinear impedance characteristics. However, compared with the PN junction, the Schottky junction capacitance is very small, down to a few tenths of a picofarad, so it is often used in high-frequency circuits, especially in microwave and millimeter-wave and submillimeter-wave circuit design. Schottky contact affects the quality and reliability of semiconductor devices and integrated circuits, so it is necessary to study Schottky contact.
[0004] Graphene has high electrical and thermal conductivity, adjustable band gap, two-dimensional structure and a thickness of up to 15000cm 2 V -1 s -1 The carrier mobility and quantum Hall effect at room temperature have triggered a research boom. Graphene has semi-metallic properties and can form a Schottky heterojunction when in contact with semiconductors, which makes it possible to replace metal electrodes with graphene, thereby reducing costs, saving resources and improving device performance.
[0005] Existing studies have shown that contacting graphene with typical semiconductor materials such as Si, ZnO, GaN, Ge, GaAs, and CdSe can further improve the performance of devices such as photodetectors, light-emitting diodes, solar cells, metal-semiconductor field-effect transistors, and sensors. However, there are van der Waals forces between graphene sheets, which are easy to agglomerate, resulting in a low Schottky barrier height of the resulting device. For example, ST Ongay et al. (ST Ongay, Graphite based Schottky diodes formed on Si, GaAs, 4H-SiC substrate. 08 (2009): 222103) used mechanical exfoliation to transfer graphene to semiconductor Si. The Schottky barrier height of graphene in contact with Si was 0.4 eV, and the ideal factor was 1.25-2.0. Dhiraj Sinha and Ji Ung Lee et al. (Dhiraj Prasad Sinha, and Ji Ung Lee, Ideal Graphene / Silicon Schottky Junction Diodes. 07 (2014): 1-14) transferred graphene prepared by chemical vapor deposition to semiconductor Si. The Schottky barrier height of graphene in contact with Si was 0.62 eV, and the ideal factor was 1.08.
[0006] In order to solve the problem of graphene's easy aggregation, researchers loaded precious metal nanoparticles and interspersed them between graphene sheets. The synergistic effect of the two inhibited aggregation, so as to better exert the excellent performance of graphene. Kun Huang (Kun Huang, Graphene coupled with Pt cubic nanoparticles for high performance, air-stable graphene-silicon solar cells. Nano Energy 32 (2017): 225-231) published a graphene silicon solar cell, in which platinum nanoparticles were first prepared by hydrothermal method, graphene film was prepared by CVD method, the graphene film was transferred to Si wafer by PMMA method, and then platinum metal nanoparticle solution was coated on the surface of graphene film. This method prepares graphene and precious metal nanoparticles separately, and uses CVD method to prepare graphene. The preparation process is complicated and costly, and the precious metal nanoparticles are unevenly dispersed in the graphene sheets, and graphene is still prone to aggregation. Summary of the invention
[0007] The present invention aims to provide a graphene-loaded noble metal composite powder, a preparation method thereof and a Schottky device. In the graphene-loaded noble metal composite powder provided by the present invention, the noble metal is evenly dispersed, the graphene is not easy to agglomerate, and the preparation method is simple and low in cost.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0009] A method for preparing a graphene-loaded noble metal composite powder comprises the following steps:
[0010] Mixing a graphene oxide solution, a noble metal precursor solution and a reducing agent to obtain a mixed solution; wherein the noble metal in the noble metal precursor exists in the form of ions;
[0011] The mixed solution is subjected to a hydrothermal reduction reaction to obtain a graphene-loaded noble metal composite powder.
[0012] Preferably, the concentration of the graphene oxide solution is 1-2 mg / mL.
[0013] Preferably, the noble metal in the graphene-loaded noble metal composite powder is gold or platinum; and the mass ratio of graphene oxide in the graphene oxide solution to the noble metal precursor in the noble metal precursor solution is 5:1 to 1:3.
[0014] Preferably, the reducing agent includes one or more of ascorbic acid, hydrazine hydrate and sodium borohydride.
[0015] Preferably, the temperature of the hydrothermal reduction reaction is 130-180° C., and the time is 10-14 hours.
[0016] The present invention provides a graphene-loaded noble metal composite powder prepared by the preparation method described in the above scheme, comprising graphene and noble metal nanoparticles loaded on the surface and between layers of the graphene; the loading amount of the noble metal nanoparticles in the composite powder is 5-60wt%.
[0017] The present invention also provides a Schottky device, comprising a semiconductor substrate and a composite powder coating loaded on the surface of the semiconductor; the composite powder is the graphene-loaded noble metal composite powder described in the above scheme.
[0018] Preferably, the loading amount of the composite powder on the surface of the semiconductor substrate is 10 to 20 mg / cm 2 .
[0019] The present invention also provides a method for preparing the Schottky device described in the above scheme, comprising the following steps:
[0020] Dispersing the graphene-loaded noble metal composite powder described in the above scheme in an alcohol solvent to obtain a composite powder dispersion;
[0021] The composite powder dispersion is coated on the semiconductor surface and dried to obtain the Schottky device.
[0022] Preferably, the alcohol solvent is anhydrous ethanol.
[0023] The present invention provides a method for preparing a graphene-loaded precious metal composite powder, comprising the following steps: mixing a graphene oxide solution, a precious metal precursor solution and a reducing agent to obtain a mixed solution; the precious metal in the precious metal precursor exists in the form of ions; and subjecting the mixed solution to a hydrothermal reduction reaction to obtain a graphene-loaded precious metal composite powder. The present invention uses graphene oxide as a raw material, and during the hydrothermal reaction, the graphene oxide and the precious metal ions can be simultaneously reduced, and the formed precious metal nanoparticles are evenly distributed on the graphene surface, which can effectively inhibit the agglomeration of graphene and enable the conductive properties of graphene to be fully exerted. The preparation method provided by the present invention has easy-to-obtain raw materials, simple steps and low cost.
[0024] Furthermore, the preparation method provided by the present invention has good control flexibility and can control the noble metal doping concentration by adjusting the mass ratio of graphene oxide and noble metal precursor.
[0025] The present invention also provides a graphene-loaded noble metal composite powder prepared by the preparation method described in the above scheme, comprising graphene and noble metal nanoparticles loaded on the surface and between the graphene layers; the loading amount of the noble metal nanoparticles in the composite powder is 5-60wt%. The composite powder provided by the present invention is not easy to agglomerate, has good conductivity, can replace noble metal electrode materials, and can be directly coated when used, without the need to transfer the graphene film, and without the need to separately prepare metal nanoparticles and the graphene film for composite, which is more convenient.
[0026] The present invention also provides a Schottky device, comprising a semiconductor substrate and a composite powder coating loaded on the surface of the semiconductor; the composite powder is the graphene-loaded noble metal composite powder described in the above scheme. The Schottky device prepared by using the graphene-loaded noble metal composite powder prepared by the present invention has a higher Schottky barrier height, and the ideal factor deviates less than the theoretical value 1. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The XRD pattern of the graphene-supported gold nanoparticle composite powder prepared in Example 1;
[0028] Figure 2 This is a SEM image of graphene-loaded gold nanoparticles prepared in Example 1, with a scale of 1 μm and a magnification of 10,000;
[0029] Figure 3The IV characteristic curve of the Schottky device prepared in Example 1;
[0030] Figure 4 This is the XRD pattern of the graphene-supported platinum nanoparticle composite powder prepared in Example 2;
[0031] Figure 5 This is a SEM image of the graphene-supported platinum nanoparticle composite powder prepared in Example 2;
[0032] Figure 6 This is the IV characteristic curve of the Schottky device prepared in Example 2. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing a graphene-loaded noble metal composite powder, comprising the following steps:
[0034] Mixing a graphene oxide solution, a noble metal precursor solution and a reducing agent to obtain a mixed solution; wherein the noble metal in the noble metal precursor exists in the form of ions;
[0035] The mixed solution is subjected to a hydrothermal reduction reaction to obtain a graphene-loaded noble metal composite powder.
[0036] The present invention mixes a graphene oxide solution, a noble metal precursor solution and a reducing agent to obtain a mixed solution. In the present invention, the diameter of the graphene oxide is preferably 0.5 to 5 μm, and the thickness is preferably 0.8 to 1.2 nm. In a specific embodiment of the present invention, the graphene oxide is purchased from Nanjing XFNANO Nanotechnology Co., Ltd.; the concentration of the graphene oxide solution is preferably 1 to 2 mg / mL, more preferably 1.3 to 1.5 mg / mL; the solvent of the graphene oxide solution is water, specifically distilled water. In the present invention, the preparation method of the graphene oxide solution is preferably: adding graphene oxide to water for ultrasonic dispersion to obtain a graphene oxide solution, and the ultrasonic dispersion time is preferably 2 hours.
[0037] In the present invention, the precious metal in the graphene-loaded precious metal composite powder is gold or platinum; the precious metal in the precious metal precursor exists in the form of ions; the precious metal precursor is preferably chloroauric acid and / or chloroplatinic acid, and the chloroplatinic acid is specifically chloroplatinic acid hexahydrate; the mass ratio of graphene oxide in the graphene oxide solution to the precious metal precursor in the chloroauric acid solution is preferably 5:1 to 1:3, and more preferably 4:1 to 1:2; in a specific embodiment of the present invention, when the precious metal precursor is chloroauric acid, the mass ratio of graphene oxide to chloroauric acid is most preferably 1:3, When the noble metal precursor is chloroplatinic acid hexahydrate, the mass ratio of the graphene oxide to chloroplatinic acid hexahydrate is most preferably 1:1; in the present invention, there is no special requirement for the concentration of the precursor solution, as long as the dissolution of the precursor can be achieved. In a specific embodiment of the present invention, the concentration of the chloroauric acid solution is preferably 5-15 mg / mL, and the concentration of the chloroplatinic acid solution is preferably 1-15 mg / mL; in a specific embodiment of the present invention, chloroauric acid or chloroplatinic acid hexahydrate is preferably added to distilled water and ultrasonicated for 5 minutes to obtain a chloroauric acid solution or a chloroplatinic acid solution.
[0038] In the present invention, the reducing agent preferably includes one or more of ascorbic acid, hydrazine hydrate and sodium borohydride, and more preferably ascorbic acid. Ascorbic acid is used as the reducing agent, which is non-toxic and harmless and will not cause environmental pollution.
[0039] In the present invention, the process of mixing the graphene oxide solution, the noble metal precursor solution and the reducing agent is preferably as follows: adding the noble metal precursor solution to the graphene oxide solution for a first ultrasonic oscillation, and then adding ascorbic acid for a second ultrasonic oscillation to obtain a mixed solution; the time for the first ultrasonic oscillation is preferably 10 minutes, and the time for the second ultrasonic oscillation is preferably 5 minutes.
[0040] After obtaining the mixed solution, the present invention performs a hydrothermal reduction reaction on the mixed solution to obtain a graphene-loaded precious metal composite powder. In the present invention, the temperature of the hydrothermal reduction reaction is preferably 130 to 180° C., more preferably 140 to 160° C., the time of the hydrothermal reduction reaction is preferably 10 to 14 hours, more preferably 11 to 12 hours; the hydrothermal reduction reaction is preferably performed in a reactor; during the hydrothermal reduction reaction, the precious metal precursor is reduced to precious metal nanoparticles, and the graphene oxide is reduced to graphene.
[0041] After the hydrothermal reduction reaction is completed, the present invention preferably cools the obtained reaction solution to room temperature and then filters it to obtain a solid product. The solid product is repeatedly centrifuged and washed with distilled water and alcohol, and then dried to obtain a graphene-loaded precious metal composite powder.
[0042] The present invention also provides a graphene-loaded noble metal composite powder prepared by the preparation method described in the above scheme, comprising graphene and noble metal nanoparticles loaded on the surface and interlayer of graphene; the loading amount of the noble metal nanoparticles in the composite powder is preferably 5-60wt%. In the present invention, the noble metal nanoparticles are preferably gold nanoparticles and / or platinum nanoparticles, more preferably gold nanoparticles or platinum nanoparticles. When the noble metal nanoparticles are gold nanoparticles, the loading amount of the gold nanoparticles in the composite powder is preferably 8-60%, and when the noble metal nanoparticles are platinum nanoparticles, the loading amount of the gold nanoparticles in the composite powder is preferably 6-53%. In the present invention, the noble metal nanoparticles are uniformly distributed in the graphene sheet, which can prevent the agglomeration of graphene and improve the conductivity of graphene.
[0043] The present invention also provides a Schottky device, comprising a semiconductor substrate and a composite powder coating loaded on the surface of the semiconductor; the composite powder is the graphene-loaded precious metal composite powder described in the above scheme; in the present invention, the loading amount of the composite powder on the surface of the semiconductor substrate is preferably 10 to 20 mg / cm 2 , more preferably 13 to 18 mg / cm 2 When the composite powder of the present invention is used to prepare a Schottky device, graphene is not easy to agglomerate, the Schottky barrier height of the device is high, and the ideal factor deviation is small.
[0044] The present invention also provides a method for preparing the Schottky device described in the above scheme, comprising the following steps:
[0045] Dispersing the graphene-loaded noble metal composite powder described in the above scheme in an alcohol solvent to obtain a composite powder dispersion;
[0046] The composite powder dispersion is coated on the surface of the semiconductor and dried to obtain the Schottky device after drying.
[0047] The present invention disperses the graphene-loaded precious metal composite powder described in the above scheme in an alcohol solvent to obtain a composite powder dispersion. In the present invention, the alcohol solvent is preferably anhydrous ethanol, and the concentration of the composite powder in the composite powder dispersion is preferably 2 to 8 mg / mL; in a specific embodiment of the present invention, the composite powder is preferably added to an alcohol solvent and then ultrasonically oscillated for 2 hours to obtain a composite powder dispersion. In the present invention, unless otherwise specified, the temperature of the ultrasonic oscillation is room temperature.
[0048] After obtaining the composite powder dispersion, the present invention coats and dries the composite powder dispersion on the surface of the semiconductor, and obtains the Schottky device after drying. In the present invention, the semiconductor is preferably a silicon wafer, and alcohol is preferably used to ultrasonically clean the silicon wafer before coating to remove surface impurities; the coating method is preferably spin coating; in a specific embodiment of the present invention, it is preferred to control the loading amount of the composite powder on the semiconductor surface by repeating the "coating-drying" process, and the wet coating is dried after each coating, and then the next coating is performed, and the coating-drying operation is repeated until the loading amount of the composite powder on the semiconductor surface reaches the requirement; the drying temperature is preferably 50°C, and the drying time for each drying is preferably 5 to 10 minutes; in a specific embodiment of the present invention, the coating-drying is repeated 20 times.
[0049] The solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0050] Example 1
[0051] (1) 50 mg of graphene oxide was ultrasonically dispersed in 50 mL of distilled water for 2 h to prepare a 1 mg / mL graphene oxide solution.
[0052] (2) Place 150 mg of chloroauric acid in 10 mL of distilled water and ultrasonicate for 5 min to obtain a chloroauric acid solution.
[0053] (3) Pour the chloroauric acid solution into the graphene oxide solution, add 100 mg of ascorbic acid after ultrasonic oscillation for 10 minutes, and then ultrasonic oscillate for another 5 minutes to obtain a mixed solution.
[0054] (4) The mixed solution prepared in step 3 is placed in a hydrothermal reactor and heated to 160° C. for 12 h. After cooling to room temperature, the mixed solution is repeatedly centrifuged and washed with distilled water and alcohol for 6 times. After drying at 70° C., a graphene-loaded gold nanoparticle composite powder is obtained.
[0055] (5) Repeatedly ultrasonically clean a silicon wafer (the size of the silicon wafer is 1 cm*1 cm, and the coating area is about 0.5 cm*1 cm) with alcohol to remove surface impurities; 20 mg of the composite powder prepared in step (4) is placed in 5 mL of anhydrous ethanol and ultrasonically vibrated for 2 h to prepare a 4 mg / mL solution, which is then spin-coated on the silicon wafer. After each spin coating, the solution is dried at 50°C, and the above operation is repeated 20 times (the coating amount each time is about 0.125 to 0.25 mL) to obtain a Schottky device.
[0056] (6) The IV characteristic curve of the Schottky device prepared in step (5) was tested using the instrument KEYSIGHT B2901A. Indium foil was placed on the silicon side, and two probes were placed on the silicon side and the graphene-loaded gold nanoparticle side, respectively. The test voltage range was -1 V to 1 V, and the test temperature was 300 K.
[0057] Figure 1 is the XRD pattern of the obtained graphene-supported gold nanoparticle composite powder. Figure 1 It can be seen that the diffraction peaks at 38.1°, 44.5°, 64.5°, 77.5°, and 81.7° are consistent with the crystal planes (111), (200), (220), (311), and (222) of the Au face-centered cubic crystal structure. There is a diffraction peak of C(002) at 21°, which is the diffraction peak of graphene.
[0058] Figure 2 The SEM image of the obtained graphene-loaded gold nanoparticles, the scale is 1 μm, the magnification is 10000, according to Figure 2 It can be seen that the gold nanoparticles are evenly distributed on the graphene surface and between the layers. The graphene has a transparent layered structure with wrinkles on the edges and a small amount of agglomerated gold nanoparticles.
[0059] Figure 3 The IV characteristic curve of Schottky device is shown in Figure 2. Figure 3 It can be seen that the current at a forward voltage of 1V is 1.27E-4, the Schottky barrier height is 0.613eV, and the ideal factor is 1.7.
[0060] Example 2
[0061] (1) 50 mg of graphene oxide was ultrasonically dispersed in 50 mL of distilled water for 2 h to prepare a 1 mg / mL graphene oxide solution.
[0062] (2) 50 mg of chloroplatinic acid hexahydrate was placed in 10 mL of distilled water and ultrasonicated for 5 min to obtain a chloroplatinic acid solution.
[0063] (3) Pour the chloroplatinic acid solution into the graphene oxide solution, add 100 mg of ascorbic acid after ultrasonic oscillation for 10 minutes, and then ultrasonic oscillate for another 5 minutes to obtain a mixed solution.
[0064] (4) The mixed solution prepared in step (3) is placed in a hydrothermal reactor and heated to 160° C. for 12 h. After cooling to room temperature, the mixed solution is repeatedly centrifuged and washed six times with distilled water and alcohol. After drying at 70° C., a graphene-loaded platinum nanoparticle composite powder is obtained.
[0065] (5) The silicon wafer was repeatedly ultrasonically cleaned with alcohol to remove surface impurities; 20 mg of the above composite powder was placed in 5 mL of anhydrous ethanol and ultrasonically vibrated for 2 h to prepare a 4 mg / mL solution, which was then spin-coated on the silicon wafer. After each spin coating, the solution was dried at 50° C. The above operation was repeated 20 times to obtain a Schottky device; in this embodiment and subsequent embodiments, the silicon wafer size and the coating amount of each coating were the same as those in Example 1.
[0066] (6) The IV characteristic curve of the Schottky device was tested using the instrument KEYSIGHT B2901A. Indium foil was placed on the silicon side, and two probes were placed on the silicon side and the graphene-loaded platinum nanoparticle side, respectively. The test voltage range was -1 V to 1 V, and the test temperature was 300 K.
[0067] Figure 4 is the XRD pattern of the obtained graphene-supported platinum nanoparticle composite powder. Figure 4 It can be seen that the diffraction peaks at 39.89°, 46.40°, 67.70°, 81.57°, and 86.03° are consistent with the (111), (200), (220), (311), and (222) crystal planes of the Pt face-centered cubic crystal structure; there is a diffraction peak of C(002) at 21°, which is the diffraction peak of graphene.
[0068] Figure 5 The SEM image of the obtained graphene-loaded platinum nanoparticle composite powder, the scale is 5 μm, and the magnification is 20000; Figure 5 It can be seen that the platinum nanoparticles have consistent particle sizes and are evenly distributed between graphene layers. Graphene has a transparent layered structure with wrinkles on the edges.
[0069] Figure 6 is the IV characteristic curve of Schottky device. Figure 6 It can be seen that the current at a forward voltage of 1V is 1.65E-4, the Schottky barrier height is 0.633eV, and the ideal factor is 2.89.
[0070] Example 3
[0071] The other conditions were the same as those in Example 2, except that the amount of chloroplatinic acid hexahydrate in step (2) was changed to 150 mg to obtain a graphene-loaded platinum nanoparticle composite powder, and then a Schottky device was prepared according to the operation of step (5) of Example 2.
[0072] The obtained composite powder was observed by SEM, and the IV characteristic curve of the Schottky device was tested according to the method of step (6) of Example 2. The results showed that the particle sizes of platinum nanoparticles were different, the graphene had slight agglomeration, and there were wrinkles on the edges; the current at the forward voltage of 1V was 9.48E-5, the Schottky barrier height was 0.628eV, and the ideal factor was 2.04.
[0073] Example 4
[0074] The other conditions were the same as those in Example 1, except that the amount of chloroauric acid was changed to 50 mg to obtain a graphene-loaded gold nanoparticle composite powder, and then a Schottky device was prepared according to the operation of step (5) of Example 1.
[0075] The obtained composite powder was observed by SEM, and the IV characteristic curve of the Schottky device was tested according to the method of step (6) of Example 1. The results showed that the gold nanoparticles were distributed on the surface and between the graphene layers, and there were wrinkles on the edges. Agglomerated gold nanoparticles existed at the wrinkles of the graphene. Because the amount of chloroauric acid used was small, the loading amount of gold nanoparticles in the composite powder was small, so the obtained graphene sheets were slightly agglomerated, and the IV characteristic curve showed that the current at the forward voltage of 1V was slightly lower than that of Example 1, which was 1.27E-4, the Schottky barrier height was slightly lower than that of Example 1, which was 0.608eV, and the ideal factor was 1.15.
[0076] Example 5
[0077] The other conditions were the same as those in Example 2, except that the amount of chloroplatinic acid hexahydrate in step (2) was changed to 10 mg to obtain a graphene-loaded platinum nanoparticle composite powder, and then a Schottky device was prepared according to the operation of step (5) of Example 2.
[0078] The obtained composite powder was observed by SEM, and the Schottky device was tested for IV characteristic curve according to the method of step (6) of Example 2. The results showed that because the amount of chloroplatinic acid used was small, the doping amount of platinum nanoparticles in the final obtained composite powder was small, the graphene was slightly agglomerated, and there were wrinkles on the edge; the IV characteristic curve test results showed that the current at the forward voltage of 1V was smaller than that of Examples 2 to 3, which was 6.57E-5, the Schottky barrier height was slightly smaller than that of Examples 2 to 3, which was 0.627eV, and the ideal factor was 1.63.
[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a Schottky device, characterized in that: The following steps are involved: Dispersing the graphene-loaded noble metal composite powder in an alcohol solvent to obtain a composite powder dispersion; coating and drying the composite powder dispersion on the surface of a semiconductor to obtain the Schottky device; The method for preparing the graphene-loaded noble metal composite powder comprises the following steps: Mixing a graphene oxide solution, a noble metal precursor solution and a reducing agent to obtain a mixed solution; wherein the noble metal in the noble metal precursor exists in the form of ions; The mixed solution is subjected to a hydrothermal reduction reaction to obtain a graphene-loaded noble metal composite powder; The noble metal in the graphene-loaded noble metal composite powder is gold or platinum; the mass ratio of graphene oxide in the graphene oxide solution to the noble metal precursor in the noble metal precursor solution is 5:1 to 1:3; the graphene-loaded noble metal composite powder includes graphene and noble metal nanoparticles loaded on the surface and between layers of the graphene; the loading amount of the noble metal nanoparticles in the composite powder is 5 to 60wt%.
2. The preparation method according to claim 1, characterized in that: The concentration of the graphene oxide solution is 1-2 mg / mL.
3. The preparation method according to claim 1, characterized in that: The reducing agent includes one or more of ascorbic acid, hydrazine hydrate and sodium borohydride.
4. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reduction reaction is 130-180° C. and the time is 10-14 hours.
5. The preparation method according to claim 1, characterized in that: The alcohol solvent is anhydrous ethanol.
6. A Schottky device, characterized in that: Prepared by the preparation method described in any one of claims 1 to 5; the Schottky device comprises a semiconductor substrate and a composite powder coating loaded on the surface of the semiconductor.
7. The Schottky device according to claim 6, characterized in that: The loading amount of the composite powder on the surface of the semiconductor substrate is 10-20 mg / cm 2 .
Citation Information
Patent Citations
Electrochemical DNA sensor based on graphene-precious metal composite and preparation method thereof
CN103033544A
Preparation method of attapulgite-based purification adsorbent
CN111346598A